Incidence of Birth Defects among Live Born Neonates at Tertiary Level Maternity Hospital in Nepal: - Shakya, Shristi; Upadhaya Subedi, Kalpana; Mishra, Megha (Journal of Nepal Paediatric Society, 2022)
Introduction: Birth defects are structural and functional anomalies that present before, at birth, or later in life. This study aimed to find out total incidence, type of structural birth defects in live born babies in Nepal. Methods: The study was conducted at a tertiary level maternity hospital in Nepal from 14 April 2018 to 13 April 2019. Data was collected on online Newborn Birth Defect data base developed by WHO South- East-Asia Regional Office. All live born babies with external and internal birth defects confirmed by radiographic, ultrasonography and echocardiography until seven days of life were included. Ethical approval was obtained from Institutional Review Committee of hospital. Results: Total of 21,564 live babies were delivered during one-year study period. Out of these, 220 (1.02%) had one or more birth defects. Number of male babies {130 (59%)} were more than female {89 (40.9%)}. 176 (80%) babies with the malformation were born to mother within age group 20 to 35 years. Of the total 220 babies with birth defects, 197 (89.5%) had isolated malformations and remaining 23 (10.4%) had sequence malformations. The most frequent malformations involved cardiovascular system 125 (56.8%) followed by gastrointestinal system 37 (16.8%), musculoskeletal system 34 (15.4%) and central nervous system 18 (8.1%). Conclusions: Incidence of overall birth defects in this study was found to be 1.02% in which cardiovascular system anomalies was the most common followed by gastrointestinal, musculoskeletal and central nervous system anomalies.